2019
DOI: 10.3389/fmicb.2018.03267
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Human Gut Bacteria Capable of Extracellular Electron Transport by Electrochemical Techniques

Abstract: Microorganisms are known to exhibit extracellular electron transfer (EET) in a wide variety of habitats. However, as for the human microbiome which significantly impacts our health, the role and importance of EET has not been widely investigated. In this study, we enriched and isolated the EET-capable bacteria from human gut microbes using an electrochemical enrichment method and examined whether the isolates couple EET with anaerobic respiration or fermentation. Upon the use of energy-rich or minimum media (w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 36 publications
(42 reference statements)
1
24
0
Order By: Relevance
“…In contrast, proteins belonging to electron transporter/ transporter were mostly up-regulated, e.g., electron transfer flavoprotein beta-subunit (1.7 ± 0.3), tryptophan synthase beta chain (1.5 ± 0.3), and oxidoreductase related to nitroreductase (2.0 ± 0.3). This was in accordance with the accelerated energy production rates in nutrient-deficient media (Figure 4), as electron transporters/transporters play critical roles in aerobic respiration and serve as the most typical way for bacteria to gain energy (Bjerg et al, 2018;Naradasu et al, 2019). Across carbon source treatments, profiles of stress-related proteins in MMC treatment behaved significantly different in comparison with others.…”
Section: Protein Profiles Involved In Stress Responsesupporting
confidence: 79%
“…In contrast, proteins belonging to electron transporter/ transporter were mostly up-regulated, e.g., electron transfer flavoprotein beta-subunit (1.7 ± 0.3), tryptophan synthase beta chain (1.5 ± 0.3), and oxidoreductase related to nitroreductase (2.0 ± 0.3). This was in accordance with the accelerated energy production rates in nutrient-deficient media (Figure 4), as electron transporters/transporters play critical roles in aerobic respiration and serve as the most typical way for bacteria to gain energy (Bjerg et al, 2018;Naradasu et al, 2019). Across carbon source treatments, profiles of stress-related proteins in MMC treatment behaved significantly different in comparison with others.…”
Section: Protein Profiles Involved In Stress Responsesupporting
confidence: 79%
“…Recent studies have revealed EET in the mammalian gut and identified other electroactive gut bacteria (6)(7)(8). Knowledge about the mechanisms behind EET in bacteria is not only of clinical relevance but very important for biotechnical applications such as in the design of microbial fuel cells.…”
mentioning
confidence: 99%
“…22 Metabolites were measured as previously described. 11 Glucose concentrations were measured by using a glucose assay kit (GAGO-20, Sigma-Aldrich) according to the manufacturer's instructions.…”
Section: Electrochemical Cell Operation and Measurementsmentioning
confidence: 99%
“…8 In particular, the identification of flavin-based enzymes in L. monocytogenes, a human pathogen, implies divergent EET mechanisms in the human microbiome. Further, Enterococcus faecalis 9,10 and two other isolates from the human gut share high homology with Klebsiella pneumoniae and Enterococcus avium, with respect to the 16S rRNA gene sequence, 11 and are capable of EET. Their EET potential may facilitate their colonization in the host environment, similar to EET in the natural environment.…”
Section: Introductionmentioning
confidence: 99%